Destination brand brilliance as a differential advantage for a tourist destination - Barkhordari, Mojgan; Shirmohammadi, Yazdan; Hashemnia , Shahram (Turyzm/Tourism, 2023)
The purpose of this article is to investigate the formation of tourist-based destination brand brilliance as a differential advantage for a destination according to Alderson’s differential theory. This will be done via content generated on social media sites by both destination management organizations and tourists, and through the mediating role of three dimensions of Aaker’s brand equity model: awareness, image and perceived quality. Alderson’s differential theory in a tourism context, and investigating the brilliance aspect of a brand, are both new research areas. Data was collected by electronically distributing questionnaires to 398 WhatsApp and Telegram users in Iran. This study confirms the relationship between tourist-generated content and destination brand brilliance through the mediating roles of awareness, image and perceived quality, but the content generated by the destination management organization to make a destination brand brilliant is only possible through the mediating roles of image and perceived quality. There is also a significant positive relationship between the perceived quality of a destination and the formation of destination brand brilliance. The findings of this research will help destination management organizations to better think about, and better manage, content generated on social media sites by organizations and tourists to form brilliance for their destination brand.